Improving the Hybrid Photovoltaic/Thermal System Performance Using Water-Cooling Technique and Zn-H2O Nanofluid - Hashim A. Hussein; Ali H. Numan; Ruaa A. Abdulrahman (International Journal of Photoenergy)
This paper presented the improvement of the performance of the photovoltaic panels under Iraqi weather conditions. The biggest problem is the heat stored inside the PV cells during operation in summer season. A new design of an active cooling technique which consists of a small heat exchanger and water circulating pipes placed at the PV rear surface is implemented. Nanofluids (Zn-H2O) with five concentration ratios (0.1, 0.2, 0.3, 0.4, and 0.5%) are prepared and optimized. The experimental results showed that the increase in output power is achieved. It was found that, without any cooling, the measuring of the PV temperature was 76°C in 12 June 2016; therefore, the conversion efficiency does not exceed more than 5.5%. The photovoltaic/thermal system was operated under active water cooling technique. The temperature dropped from 76 to 70°C. This led to increase in the electrical efficiency of 6.5% at an optimum flow rate of 2 L/min, and the thermal efficiency was 60%. While using a nanofluid (Zn-H2O) optimum concentration ratio of 0.3% and a flow rate of 2 L/min, the temperature dropped more significantly to 58°C. This led to the increase in the electrical efficiency of 7.8%. The current innovative technique approved that the heat extracted from the PV cells contributed to the increase of the overall energy output.